Analisis Pengaruh Net Profit Margin (NPM) dan Earning Per Share (EPS) Terhadap Return Saham pada PT. Akasha Wira Internasional Tbk - Faradila, Putri Aulia; Puji Muniarty; Juwani (Jurnal Ilmu Manajemen Retail Universitas Muhammadiyah Sukabumi, 2025)
From 2014 to 2023, this research will track PT. Akasha Wira Internasional Tbk stock returns by examining the relationship between Net Profit Margin (NPM) and Earnings Per Share (EPS).  An important metric for investors to consider when assessing the financial health and future profitability of a firm is its stock return.  The operational efficiency and firm profitability are reflected in NPM and EPS, which are chosen as independent variables.  Using multiple linear regression analysis, this study employs a quantitative associative method.  The Indonesia Stock Exchange (IDX) listed company's yearly financial statements were used as secondary data.  Partially, the data demonstrate that NPM is not significantly related to stock return, while EPS is.  Stock return is significantly affected by both NPM and EPS at the same time.  With a coefficient of determination (R²) of 65.7%, NPM and EPS account for 65.7% of the variance in stock return, while other variables account for the remaining 34.3%.  According to the findings, EPS is an important metric for investors to use when deciding whether or not to put money into a company, and businesses should aim to increase their profits per share in order to entice more investors.